Cultural appropriation in fashion and entertainment / Yuniya Kawamura, Jung-Whan Marc de Jong. - Kawamura, Yuniya, 1963-; De Jong, Jung-Whan Marc (Bloomsbury Visual Arts, 2022)
Is it ever appropriate to 'borrow' culturally inspired ideas? Who has ownership over intangible culture? What role does power inequality play? These questions are often at the center of heated public debates around cultural appropriation, with new controversies breaking seemingly every day. This book offers a sociological perspective on the debate, exploring appropriation of cultures embedded in race, ethnicity, class, sexuality, and religion in entertainment as well as the clothing, textiles, jewelry, accessories, hairstyles, and tattoos we wear. Case studies are drawn from K-pop, Bollywood dance, J-pop, Bhangra music, Jamaican reggae, hip hop and EDM fashion to explore how, when, and why cultural borrowing or appreciation can become cultural appropriation. There's also discussion of subcultural territories that extend beyond geography, race and ethnicity, such as cosplay and LGBTQI+ communities.